Maintained Hydration Status After a 24-h Winter Mountain Running Race Under Extremely Cold Conditions - Chlíbková, Daniela; Nikolaidis, Pantelis T.; Rosemann, Thomas; Knechtle, Beat; Bednář, Josef (Frontiers in Physiology, 2019)
Background: To date, no study has examined the hydration status of runners competing in a 24-h winter race under extremely cold environmental conditions. Therefore, the aim was to examine the effect of a 24-h race under an average temperature of 14.3°C on hydration status. Methods: Blood and urine parameters and body mass (BM) were assessed in 20 finishers (women, n = 6; men, n = 14) pre- and post-race. Results: Five (25%) ultra-runners had lower pre-race plasma sodium [Na+] and 11 (52%) had higher pre-race plasma potassium [K+] values than the reference ranges. Post-race plasma [Na+], plasma osmolality, urine osmolality and urine specific gravity remained stable (p ˃ 0.05). The estimated fluid intake did not differ (p ˃ 0.05) between women (0.30 ± 0.06 L/h) and men (0.46 ± 0.21 L/h). Runners with a higher number of completed ultra-marathons (r = -0.50, p = 0.024) and higher number of training kilometers (r = -0.68, p = 0.001) drank less than those with lower running experience. Pre-race and post-race plasma [Na+] were related to plasma osmolality (r = 0.65, p = 0.002, r = 0.69, p < 0.001, respectively) post-race, but not to fluid intake (p ˃ 0.05). BM significantly decreased post-race (p = 0.002) and was not related to plasma [Na+] or fluid intake (p ˃ 0.05). Post-race hematocrit and plasma [K+] decreased (p < 0.001) and transtubular potassium gradient increased (p = 0.008). Higher pre-race plasma [K+] was related to higher plasma [K+] loss post-race (p = -0.85, p < 0.001). Conclusions: Hydration status remained stable despite the extremely cold winter weather conditions. Overall fluid intake was probably sufficient to replenish the hydration needs of 24-h runners. Current recommendations may be too high for athletes competing in extremely cold conditions.